Feasible Policy Evaluation by Design: A Randomized Synthetic Stepped-Wedge Trial of Mandated Disclosure in King County. (February 2020) - Handan-Nader, Cassandra; Ho, Daniel E.; Elias, Becky
Evidence-based policy is limited by the perception that randomized controlled trials (RCTs) are expensive and infeasible. We argue that carefully tailored research design can overcome these challenges and enable more widespread randomized evaluations of policy implementation. We demonstrate how a stepped-wedge (randomized rollout) design that adapts synthetic control methods overcame substantial practical, administrative, political, and statistical constraints to evaluating King County's new food safety rating system. The core RCT component of the evaluation came at little financial cost to the government, allowed the entire county to be treated, and resulted in no functional implementation delay. The case of restaurant sanitation grading has played a critical role in the scholarship on information disclosure, and our study provides the first evidence from a randomized trial of the causal effects of grading on health outcomes. We find that the grading system had no appreciable effects on foodborne illness, hospitalization, or food handling practices but that the system may have marginally increased public engagement by encouraging higher reporting.